Hormonal (cortical-gonadotropic axis) and physical changes with two years intense exercise training in elite young soccer players - Hammami, M. A.; Ben Abderrahman, A.; Hackney, A. C.; Kebsi, W.; Owen, A. L.; Nebigh, A.; Racil, G.; Tabka, Z.; Zouhal, H. (The Journal of Strength and Conditioning Research, 2017)
The aim of this study was to investigate the effects of 2 soccer-training seasons on physical fitness and hormone concentrations in elite youth soccer players. Twenty male elite soccer players (SP, age 14.5 ± 0.4 years) and 20 male control subjects (CS, age 14.3 ± 0.3 years) participated in the study. Anthropometric measurements, aerobic (Yo-Yo Intermittent Recovery Test Level 1 [YYIRT1]) and anaerobic soccer relevant performances (jump and sprint tests), blood testosterone (T), cortisol (C), sex hormone binding globulin (SHBG), and T/C ratio were assessed 5 times (from T0 to T4) during 2 competitive seasons. Significant differences from basal values (?) of T, SHBG, and C between SP and CS were observed (p < 0.01). Additionally, T and T/C ratio changes were positively correlated with physical performance (p = 0.05). In conclusion, as expected, higher T concentration and greater power performance were observed in the soccer players group compared with controls. Our findings also show that the T concentrations and power performance outcomes co-vary positively over the 2 soccer seasons in soccer players.